Our politeuma is in heaven! : Paul's polemical engagement with the "enemies of the cross of Christ" in Philippians 3:18-20 - Sergienko, Gennadi A. (Carlisle, Cumbria. Langham Monographs, 2013)
Paul's letters to Philippians show us that this rather outspoken man had plenty of opportunity and cause to aggravate his Christian contemporaries. However, for Paul to use such hostility, as he does in Philippians 3:18-20, and to name people as "enemies" shows us that we should take note and try to understand the meaning behind his statement. In this work the author asks: who were these enemies? What did they do wrong? Why did they deserve destruction? In search of these questions the investigation looks to the early Christian communities and their formation within the socio-political realities of the urban centers of the Roman Empire. Through this we learn a great deal about the uneven and complex dynamics of the early Christian community and a deep understanding of Paul's warning to them
Keywords: Bible.-- Philippians, III, 18-20 - Language, style; Paul, the Apostle, Saint; Paul, the Apostle, Saint.-- Political and social views